Plant parasitic nematode communities associated with the crop banana (Musa spp.) at Attappady Tribal hill area, India - Ashfak A. ODALA; Rasmi A. RAMANATHAN; Usman ARERATH (Notulae Scientia Biologicae, 2020)
Attappady is a region of immense biological importance comes under the Nilgiri Biosphere Reserve area of India at Palakkad district. Biodiversity study of this hill area has great importance in conservative science. Except a national range study for nematode fauna of banana (Musa spp.) in Indian banana fields, a detailed survey of this agriculturally and environmentally important area has not reported till now. The diversity analysis of plant parasitic nematodes was done with samples taken from rhizosphere soil and roots of banana at this area. Comparing with the reported nationwide study the present study newly reported the presence of Aphelenchus spp., Dorylaimoides spp., Hoplolaimus spp., Rotylenchulus spp., Tylenchorynchus spp. and Tylenchus spp. from the crop banana other than the already reported one’s such as Helicotylenchus spp., Meloidogyne spp., Pratylenchus spp. and Radopholus spp. The analysis of nematode genera in different banana cultivars such as Musa × paradisiaca L. (AAB) ‘Nendran’, Musa acuminata Colla (AAA) ‘Robusta’, Musa acuminata Colla (AA) ‘Kadali’ and Musa × paradisiaca L. (Mysore AAB) ‘Poovan’ revealed differences in the reaction to attack between genotypes, and that the cultivar ‘Nendran’ was the most susceptible one to plant parasitic nematodes.